Об’єктивні передумови формування аграрного права України - Коваленко, Т.; Kovalenko, T. (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті аналізуються природно-кліматичні, економічні та правові фактори, які зумовили виникнення та становлення у 90-х роках ХХ ст. аграрного права України як об’єктивно сформованої, самостійної та цілісної галузі національної правової системи. Специфіка агропромислового комплексу як галузі народного господарства, його роль та значення в економіці держави, особливості процесу сільськогосподарського виробництва, зокрема його істотна залежність від природно-кліматичних умов, необхідність врахування біологічних законів розвитку живих організмів як основи аграрного виробництва, тісний взаємозв’язок ефективності сільськогосподарського виробництва із розвитком соціальної сфери села тощо є об’єктивними економічними передумовами формування відокремленого правового регулювання відносин у сфері сільськогосподарського виробництва України та пов’язаних із ним сферах In the article the author proves that the emergence and formation of Agricultural law as an objectively existing, independent and holistic branch of law in Ukraine since 1991 is due to a number of objective conditions, the determination of which makes it possible to more precisely illuminate its nature, and to identify the driving forces and mechanisms that led to the appearance of Ukrainian Agricultural law in the national legal system. To the objective prerequisites for the formation of Agricultural law of Ukraine author includes climatic, economic and legal factors that contribute to the emergence and formation of this branch of law regardless of the influence of man, society and the state on the development of agricultural relations. It is proved that the presence of the unique reserves of black earth and favorable for the conduct of agricultural production of climate - on the one hand, as well as high dependence on climatic conditions, the seasonality of such production, the need to consider the biological laws of development of living organisms as a basis for agricultural production, a strong correlation of agricultural production efficiency with the development of the social sphere of the village - on the other hand, objectively determine the special public-legal influence on the relations arising in the process of production of food and food raw materials.
Objective Preconditions of Agricultural Law of Ukraine Formation
Keywords: аграрне право України; аграрні правовідносини; аграрна реформа; формування аграрного права; передумови формування аграрного права; agricultural law of Ukraine; agricultural relationship; agricultural reform; formation of agricultural law; preconditions of formation of agricultural law